Misperceived Positions of Interlaced Fingers. (September 2019) - Anstis, Stuart
Interlacing one's fingers can cause misperception of finger positions. Observer's (O's) fingers were interlaced in six different ways and experimenter (E) tapped two adjacent fingers in quick succession (e.g., tapping the right middle finger then the left ring finger). O had to state the perceived direction in which the tapping occurred, and errors were recorded. When hands were well separated, touching two adjacent fingers of one hand gave error rates of only 2.4%, and touching a finger on one hand then the other gave error rates of only 3.4%. Interlacing the fingers as if in prayer increased error rates to 9%. When hands were superimposed with finger pointing away from O's body, error rates rose further to 30%. Observers knew which fingers were which, but they were confused about exactly where their fingers were. Thus, somatotopic was greatly superior to spatiotopic localization.